Privacy-Enhancing Aggregation Techniques for Smart Grid Communications - Lu, Rongxing (Wireless Networks, 2016)
This book provides an overview of security and privacy issues in smart grid communications, as well as the challenges in addressing these issues. It also introduces several privacy enhancing aggregation techniques including multidimensional data aggregation, subset data aggregation, multifunctional data aggregation, data aggregation with fault tolerance, data aggregation with differential privacy, and data aggregation with integrity protection. Offering a comprehensive exploration of various privacy preserving data aggregation techniques, this book is an exceptional resource for the academics, researchers, and graduate students seeking to exploit secure data aggregation techniques in smart grid communications and Internet of Things (IoT) scenarios.